Label-Free, Novel Electrofluidic Capacitor Biosensor for Prostaglandin E2 Detection toward Early and Rapid Urinary Tract Infection Diagnosis - Ganguly, Antra; Ebrahimzadeh, Tahmineh; Zimmern, Philippe; De Nisco, Nicole J; Prasad, Shalini (ACS sensors, 2022)
Urine Prostaglandin E2 (PGE2) has been identified as an attractive diagnostic and prognostic biomarker for urinary tract infection (UTI). This work demonstrates the use of PGE2 as a biomarker for rapid and label-free testing for UTI. In this work, we have developed a novel electrofluidic capacitor-based biosensor that can used for home-based UTI management with high accuracy in less than 5 min for small volume urine samples (<60 μL). The PGE2 biosensor works on the principle of affinity capture using highly specific monoclonal PGE2 antibody and relies on non-faradaic electrical impedance spectroscopy (EIS) and Mott–Schottky (MS) for quantifying subtle variations in PGE2 levels expressed in human urine (pH 5–8). Dynamic light scattering experiments were performed to characterize surface charge properties and the impact of bulk interferents on the interfacial modulation of electrical properties due to binding and urine pH variations. Binding chemistry between the key elements of the immunosensor stack was validated using attenuated total reflectance-Fourier transform infrared spectroscopy and surface plasmon resonance studies. Linear calibration dose responses were obtained for PGE2 for both EIS and MS. The sensor reliably distinguished between UTI negative and UTI positive cases for both artificial (pH 5–8) and pooled human urine samples. The sensor was not found to cross-react with Prostaglandin D2, a structurally similar interferent, and other abundant urine interferents (urea and creatinine). Human subject studies confirmed the validity of the sensor for robust and accurate UTI diagnosis. This work can be extended to achieve easy, reliable, and rapid home-based UTI management, which can consequently help physicians with timely and appropriate administration of therapy to improve patient outcomes and treatment success.